2020
DOI: 10.1634/theoncologist.2020-0759
|View full text |Cite
|
Sign up to set email alerts
|

A Phase I Trial of Trametinib in Combination with Sorafenib in Patients with Advanced Hepatocellular Cancer

Abstract: The combination of trametinib and sorafenib has an acceptable safety profile, albeit at doses lower than approved for monotherapy. • Maximum tolerated dose is trametinib 1.5 mg daily and sorafenib 200 mg twice daily. • The limited anticancer activity observed in this unselected patient population does not support further exploration of trametinib plus sorafenib in patients with hepatocellular carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 15 publications
1
12
0
Order By: Relevance
“…3C-E). Interestingly, there are indeed some reports on the synergistic application of above inhibitors and other anticancer drugs for the treatment of HCC [46][47][48][49], which supported the original intention of our study, i.e., to find key TME-related targets for the combination targeted therapy. Collectively, we confirmed that the integrin-FAK-Src, MEK-ERK, and PI3K-AKT pathways were involved in microstructure formation.…”
Section: Hiis Activated Integrin-α 5 β 1 Downstream Signalingsupporting
confidence: 83%
“…3C-E). Interestingly, there are indeed some reports on the synergistic application of above inhibitors and other anticancer drugs for the treatment of HCC [46][47][48][49], which supported the original intention of our study, i.e., to find key TME-related targets for the combination targeted therapy. Collectively, we confirmed that the integrin-FAK-Src, MEK-ERK, and PI3K-AKT pathways were involved in microstructure formation.…”
Section: Hiis Activated Integrin-α 5 β 1 Downstream Signalingsupporting
confidence: 83%
“…Thus, ferroptosis likely plays an important role in the occurrence and development of HCC. 186,187 According to recent studies, the effect of the p62-Keap1-NRF2 signaling pathway on HCC is closely related to ferroptosis induced by elastin/sorafenib. Interference with p62 (the substrate adaptor) enhances ferroptosis induced by erastin/sorafenib in HCC cells.…”
Section: Hepatocellular Carcinomamentioning
confidence: 99%
“…[115][116][117][118][119] However, the efficacy of combination therapy is not supported by all studies. 120 Clinical trials demonstrated that the MEK inhibitor, trametinib, combined with the multitargeted TKI midostaurin can improve the prognosis of patients with FLT3-TKI-resistant AML. 121 In addition, P21 (RAC1)-activated kinase 2 (PAK), whose overexpression is related to lenvatinib resistance in some types of TC is also a downstream molecule of RAS.…”
Section: Mechanisms Of Tki Resistancementioning
confidence: 99%